The Role of Microfinance in the Entrepreneurial Development in Pakistan - Raza, Hasan (Archives of Business Research, 2017)
This research was done with the prime objective to explore the role and effectiveness of microfinance in developing entrepreneurship. For economic growth and its sustainability, microfinance is deemed as one of the most necessary and operative mechanism. A sample of three hundred (350) respondents was selected based upon the basic criteria to be micro entrepreneurs using a Likert scale analysis. The facility of microfinance provision to young unemployed persons, unemployed women or poor persons has proved a tool for entrepreneurial development, reduce poverty through employment opportunity creation and a lead towards economic improvement and develop the nation. The need of entrepreneurship gets high importance on micro level due to the reason that upcoming innovations can save the resources and those resources can be utilized in more productive manner with better results.